2004
DOI: 10.1103/physreva.69.033810
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of elliptically polarized states in vertical-cavity-surface-emitting lasers

Abstract: We study the elliptically polarized states in the spin-flip model for vertical-cavity-surface-emitting lasers. The stability analysis reveals some unexpected features. In correspondence with particular values of the birefringence parameter, which are shown to scale very simply with the ratio of the spin-flip rate to the linewidth enhancement factor, the stability domain can be quite large. Moreover, in some cases two different dynamical regimes can arise from the destabilization of the elliptically polarized s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…To detect such folding, we use the following approach. After applying PCA, we reconstruct the 5-D states trajectories using only a subset of the calculated PCs using (7). We then compare the distance between the data point and its closest neighbor in the initial and reconstructed 5-dimension state trajectories space.…”
Section: Optimal Embedding Of Polarization Chaosmentioning
confidence: 99%
See 1 more Smart Citation
“…To detect such folding, we use the following approach. After applying PCA, we reconstruct the 5-D states trajectories using only a subset of the calculated PCs using (7). We then compare the distance between the data point and its closest neighbor in the initial and reconstructed 5-dimension state trajectories space.…”
Section: Optimal Embedding Of Polarization Chaosmentioning
confidence: 99%
“…Their main drawback has been identified early on as polarization instabilities [1]: the most striking example being polarization switching (PS) events where the linearly polarized laser light suddenly rotates by 90 • [2]- [6]. But a wide range of behaviour have been reported including elliptical polarization [7], noise-induced hopping [8], [9] and even chaotic dynamics with the so-called polarization chaos [10], [11]. Although these instabilities have been first studied to be avoided [12], [13], it was also remarked Manuscript received XXX This work has been supported by the Research Foundation -Flanders (FWO) through project REFLEX (krediet aan Navorsers, 1530318N) and the post-doctoral fellowship of MV, and by the METHUSALEM program of the Flemish Governments.…”
Section: Introductionmentioning
confidence: 99%
“…For γ a = 0, the expression becomes much more complicated [29], yet (6) remains an excellent approximation in practice. Thus, µ x would therefore be a lower bound of the region of chaotic dynamics in terms of injection current.…”
Section: Insight On Chaotic Vcsel Behaviormentioning
confidence: 99%
“…SFM has later been extended to include cavity anisotropies. [11][12][13] The SFM steady-states have been extensively studied by means of asymptotic methods or direct numerical integration [11][12][13][14][15][16][17] and it appears that SFM allows for linearly and elliptically polarized states. The stability analysis of these steady-states revealed that both type I and type II PSs are possible in the framework of SFM, the inclusion of additional parameters (e.g.…”
Section: Introductionmentioning
confidence: 99%